A Rare Case Report of Carcinoma Gall Bladder with Brain Metastasis in 18 Year Old Male - Mahajan, Divya; Kamaraj, Theepanraj (Asian Pacific Journal of Cancer Biology, 2023)
Introduction: Worldwide carcinoma gall bladder is 22nd most common cancer and 17th most common cause of death according to GLOBOCAN 2018 data. In 2018, the estimated incidence was 97,000 for men and 122,000 for women. Risk of carcinoma gall bladder from birth till 74 year is 0.26% for women and 0.25% for men. Here we are reporting a case of carcinoma gall bladder of 18 year old male who presented to us in opd with extensive brain metastasis and liver metastasis. Case presentation: This case report refers to 18 year old male presented to us with chief complaint of pain in right hypochondrium for 20 days and history of headache and vomiting since 4 days. CECT whole abdomen suggestive of a 5.9*3.9*3.2 mass arising from body of gall bladder extending into segment V of liver. CEMRI BRAIN suggestive of 3.2*3 cm lesion in left frontoparietal region of brain parenchyma. USG guided FNAC from gall bladder suggestive of poorly differentiated adenocarcinoma. Patient was treated by whole brain RT on Co-60 by German helmet technique planned 30Gy/10#. Conclusion: This case adds to our knowledge that Gall bladder cancer is extremely rare malignancy in children. These tumors are not associated with gall stones in this age group and further studies must be done to evaluate the risk factors in younger age group.